Prenatal factors associated with breach of the basic vaccination scheme in under 5 years of age - Isidro-Ríos, Trinidad L. (2021)
Objective: To determine the prenatal risk factors associated with the failure to comply with the basic vaccination scheme in children under 5 years of age, based on the Demographic and Family Health Survey (ENDES) of 2018. Materials and Methods: It is an observational, retrospective, analytical and transversal study. We study the sample of the National Demographic and Health Survey (ENDES) for 2018 that includes 18 104 children between 1 and 5 years with health card seen in the interview, finding the results in the INEI surveys. The files containing the vaccination scheme questionnaires are selected and the data processed with SPSS version 25. The statistical processing is analytical and descriptive, bivariate and multivariate with the help of STATA v16 and Excel 2016. Results: There was a final sample of 18,104 children between 1 to 5 years old in 2018. The multivariate analysis found the association of non-compliance with the vaccination schedule with the mother's age (p value = <0.01, PR = 1.20, CI = 1.13 - 1.28), the number of controls inadequate (p value = <0.01, PR = 1.28, CI = 1.23 - 1.33) and the pregnant woman did not receive the tetanus vaccine during pregnancy (p= <0.01, RP= 1.16, CI= 1.12 - 1.20). No such association was found with the place of residence, wealth index and natural region. Conclusions: The prenatal risk factors associated with the failure to comply with the basic vaccination scheme in children under 5 years of age were maternal age, the number of inadequate prenatal check-ups and the pregnant woman who had not received the tetanus vaccine.